Learning Systems Engineering by Teaching It. (28th October 2015) - Armstrong, James; Wade, Jon
Abstract: Research has been conducted to learn how systems engineers develop their expertise. One finding is that many expert systems engineers credit teaching for part of their development. This paper summarizes the overall research results and expands on this particular finding. It addresses factors related to learning by teaching and how the systems engineering community can better take advantage of this mode of learning.